Protein and peptide composition of male accessory glands of Apis mellifera drones investigated by mass spectrometry - Gorshkov, Vladimir; Blenau, Wolfgang; Koeniger, Gudrun; Römpp, Andreas; Vilcinskas, Andreas; Spengler, Bernhard; Justus Liebig University Giessen (My University, 2015)
In honeybees, reproductive females usually mate early in their life with more than 10 males in free flight, often within 10 minutes, and then store male gametes for up to five years. Because of the extreme polyandry and mating in free flight special adaptations in males are most likely. We present here the results of an investigation of the protein content of four types of male reproductive glands from the Western honeybee (Apis mellifera) drone, namely seminal vesicles (secretion in ejaculate), as well as bulbus, cornua and mucus glands (secretions for the mating plug). Using high resolution and accuracy mass spectrometry and a combination of database searching and de novo sequencing techniques it was possible to identify 50 different proteins in total, inside all mentioned glands, except in the mucus gland. Most of the proteins are unique for a specific gland type, only one of them (H9KEY1/ATP synthase subunit O) was found in three glands, and 7 proteins were found in two types of glands. The identified proteins represent a wide variety of biological functions and can be assigned to several physiological classes, such as protection, energy generation, maintaining optimal conditions, associated mainly with vesicula seminalis; signaling, cuticle proteins, icarpin and apolipoproteins located mainly in the bulbus and cornua glands; and some other classes. Most of the discovered proteins were not found earlier during investigation of semen, seminal fluid and tissue of reproductive glands of the bee drone. Moreover, we provide here the origin of each protein. Thus, the presented data might shed light on the role of each reproductive gland.
Keywords: ddc:540